The gender of caste : representing Dalits in print - Gupta, Charu
"Caste and gender are forms of social difference that typically have been addressed in isolation from each other: a presumptive maleness is present in most studies of Dalits, and a presumptive upper-casteness is present in many feminist studies of colonial India. The Gender of Caste enters new territory in its exploration of the gender of caste through representations of Dalits in print media in colonial north India. Among its subjects are images of Dalit women as victims and vamps, the construction of Dalit masculinities, religious conversion as an alternative to entrapment in the Hindu caste system, and the plight of indentured servants. An array of textual and pictorial material pertaining to Dalits is drawn from reformist, popular, and didactic literature; police reports; missionary records; and cartoons. The book shows how differentials of gender were critical in structuring patterns of domination and subordination. Through a gendered Dalit perspective, it historicizes axes of gender, caste, class, and community identities. Representations in print are used as a critical tool to examine depictions of Dalits by colonizers, nationalists, reformers, and Dalits themselves"--Provided by publisher.